Inhibition of Activated Coagulation Factor VII by Normal Human Plasma - Dahl, P E; Abildgaard, U; Larsen, M L; Tjensvoll, L (Thrombosis and Haemostasis, 1982)
An amidolytic assay system with tissue thromboplastin (Tpl), purified coagulation factors VII and X, and the chromogenic substrate S-2222 was developed. Antithrombin III (AT) accounts for about one third of the total inhibition exerted by normal plasma in this test system. This effect of AT was prevented by adding purified AT blocking antibodies. Normal plasma and serum showed approximately similar inhibitory effects. The inhibition was probably directed against activated factor VII (F VIIa). Gel filtration of adsorbed normal plasma on Ultrogel AcA 34 showed three inhibitory peaks which were different from AT.
Keywords: Key words Factor VII; Coagulation inhibitors; Chromogenic substrates